2017
DOI: 10.1073/pnas.1617722114
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor pathway evolution in deuterostomes

Abstract: Animals have evolved an array of pattern-recognition receptor families essential for recognizing conserved molecular motifs characteristic of pathogenic microbes. One such family is the Toll-like receptors (TLRs). On pathogen binding, TLRs initiate specialized cytokine signaling catered to the class of invading pathogen. This signaling is pivotal for activating adaptive immunity in vertebrates, suggesting a close evolutionary relationship between innate and adaptive immune systems. Despite significant advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Group 23 is formed mostly by chordate proteins, but also includes representative cnidarian TIRs, several TIRs of lower deuterostomes (both echinoderms and hemichordates), and TIRs of two protostome phyla, i.e., Annelida and Brachiopoda. These organisms typically have one gene encoding a protein with a group 23 TIR; however, some species of protostomes and deuterostomes, including echinoderms, may have multiple genes encoding MyD88-like proteins (Ren et al 2014;Tassia et al 2017). A typical MyD88-like protein has two protein interaction domains, an N-terminal death domain, and a C-terminal TIR (Hardiman et al 1996).…”
Section: Groups 23 and 32: Myd88-like Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 23 is formed mostly by chordate proteins, but also includes representative cnidarian TIRs, several TIRs of lower deuterostomes (both echinoderms and hemichordates), and TIRs of two protostome phyla, i.e., Annelida and Brachiopoda. These organisms typically have one gene encoding a protein with a group 23 TIR; however, some species of protostomes and deuterostomes, including echinoderms, may have multiple genes encoding MyD88-like proteins (Ren et al 2014;Tassia et al 2017). A typical MyD88-like protein has two protein interaction domains, an N-terminal death domain, and a C-terminal TIR (Hardiman et al 1996).…”
Section: Groups 23 and 32: Myd88-like Proteinsmentioning
confidence: 99%
“…Group 37: TRIF-like TIRs Group 37 consists of TIR domains related to those of TRIF, also known as TICAM-1, a TLR adapter protein that participates in TLR3 and TLR4 signaling, leading to a robust activation of type I interferons (Oshiumi et al 2003;Yamamoto et al 2002). TRIF-like proteins occur in vertebrates (Tassia et al 2017). Group 37 consists exclusively of chordate TIRs (Supplemental Fig.…”
Section: Group 23 Residue Patterns and Structural Featuresmentioning
confidence: 99%
“…This might be the reason why there are less TLRs found in our study than the genomic prediction. Interestingly, if we remove 3 mccTLR sequences in B. floridae from our list, the total number of TLRs would be the same as reported by Tassia et al which identified 19 TLRs ( 56 ). Moreover, the RT-PCR analysis showed that all the 30 TLRs of B. lanceolatum were truly expressed in adult animals.…”
Section: Discussionmentioning
confidence: 98%
“…TLR-induced activation of the NF-jB pathway, for instance, is shared between mammals, insects and sea urchins. [24][25][26] Furthermore, there is evidence to suggest that the molecular control of the 3-TM outlined previously is evolutionarily ancient. Myc and its homologs have important roles in controlling proliferation in stem cell and gamete populations in the metazoan Hydra.…”
Section: The Autonomous B-cell Programmentioning
confidence: 95%
“…22,23 The components and mechanism of the 3-TM are illustrated in Figure 1a, b to highlight how it leads to a canonical immune response pattern. As a result of the absence of the generation of any additional specialized cell types, as well as the ancient origin of TLRs, 24,25 it appears that the TLR9-induced B-cell program provides a window back to simpler organisms that relied on innate immune recognition to initiate protective responses that could include limited cell expansion.…”
Section: The Autonomous B-cell Programmentioning
confidence: 99%